Simultaneous Delivery of Electrostatically Complexed Multiple Gene-Targeting siRNAs and an Anticancer Drug for Synergistically Enhanced Treatment of Prostate Cancer - Choi, Eunshil; Yoo, Wonjae; Park, Jae Hyung; Kim, Sehoon (AMER CHEMICAL SOC, 2018)
Simultaneous silencing of multiple apoptosis-related genes is an attractive approach to treat cancer. In this article, we present a multiple gene-targeting siRNA/drug delivery system for prostate cancer treatment with a high efficiency. Bcl-2, survivin, and androgen receptor genes involved in the cell apoptosis pathways were chosen as silencing targets with three different siRNAs. The colloidal nanocomplex delivery system (<10 nm in size) was formulated electrostatically between anionic siRNAs and a cationic drug (BZT), followed by encapsulation with the Pluronic F-68 polymer. The formulated nanocomplex system exhibited sufficient stability against nuclease-induced degradation, leading to successful intracellular delivery for the desired therapeutic performance. Silencing of targeted genes and apoptosis induction were evaluated in vitro on human prostate LNCaP-LN3 cancer cells by using various biological analysis tools (e.g., real-time PCR, MTT cell viability test, and flow cytometry). It was demonstrated that when the total loaded siRNA amounts were kept the same in the nanocomplexes, the simultaneous silencing of triple genes with co-loaded siRNAs (i.e., Bcl-2, survivin, and AR-targeting siRNAs) enhanced BZT-induced apoptosis of cancer cells more efficiently than the silencing of each single gene alone, offering a novel way of improving the efficacy of gene therapeutics including anticancer drug.
Keywords: CO-DELIVERY; RNAI THERAPEUTICS; IN-VIVO; ANDROGEN RECEPTOR; CELL-GROWTH; APOPTOSIS; NANOPARTICLES; INTERFERENCE; PROTEINS; SURVIVIN